(untitled) (El-Wahat Journal for Research and Studies, 2026)
This study explores the importance of preserving the intangible folklore of the Ahaggar region in southern Algeria, emphasizing the urgent need to protect it from cultural erosion caused by globalization and rapid technological change. These factors pose a threat to Arab-Islamic identity and cultural uniqueness. Algeria’s diverse cultural and intellectual legacy, shaped by the succession of civilizations and historical events, highlights the responsibility of researchers in safeguarding national identity. The research underscores the necessity of preserving intangible folk traditions and calls upon authorities to implement immediate strategies, including the creation of museums and cultural centers dedicated to documentation and preservation. It also advocates support for individual and grassroots efforts in heritage conservation. The study concludes that sustainable preservation depends on active transmission across generations, and on collective awareness and participation. Ensuring continuity requires reviving traditions, raising awareness, and removing barriers that threaten the survival of this rich cultural heritage.